2014
DOI: 10.1021/es503088x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Nitrous Acid and Nitrogen Dioxide from Nitrate Photolysis in Acidic Aqueous Solutions

Abstract: Nitrate (NO3(-)) is an abundant component of aerosols, boundary layer surface films, and surface water. Photolysis of NO3(-) leads to NO2 and HONO, both of which play important roles in tropospheric ozone and OH production. Field and laboratory studies suggest that NO3¯ photochemistry is a more important source of HONO than once thought, although a mechanistic understanding of the variables controlling this process is lacking. We present results of cavity-enhanced absorption spectroscopy measurements of NO2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
205
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(219 citation statements)
references
References 111 publications
14
205
0
Order By: Relevance
“…We note that, if HONO production is greater than assumed at Dome C, following the recent laboratory study of Scharko et al (2014), this will not change the main conclusions of this study. Indeed, the photolytically produced HONO will be photolyzed to form NO in the atmosphere and this NO would simply enter the NO / NO 2 cycles, where oxygen isotopes are reset.…”
Section: Validation Of the Macroscopic Fluxesmentioning
confidence: 61%
“…We note that, if HONO production is greater than assumed at Dome C, following the recent laboratory study of Scharko et al (2014), this will not change the main conclusions of this study. Indeed, the photolytically produced HONO will be photolyzed to form NO in the atmosphere and this NO would simply enter the NO / NO 2 cycles, where oxygen isotopes are reset.…”
Section: Validation Of the Macroscopic Fluxesmentioning
confidence: 61%
“…In addition to the heterogeneous NO 2 reaction, Bejan et al (2006) observed HONO formation during irradiation of nitrophenols. Photolysis of nitrate or nitric acid generates HONO as well (Baergen and Donaldson, 2013;Scharko et al, 2014;Zhou et al, , 2011. Contrary to the detected missing HONO source near the ground, recent airborne measurements (500-1200 m a.g.l., above ground level) observed HONO concentrations, which could be explained by gas-phase reactions only (Li et al, 2014;Neuman et al, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, other recently proposed HONO sources will have a minor contribution. Aqueous solutions in which HONO yields from nitrate photolysis may be enhanced by organics (Scharko et al, 2014) will not be important for the urban conditions investigated in this study as there are no aqueous surfaces in the surrounding area. Recently, in the study of Rutter et al (2014), a gas phase reduction of HNO 3 by VOCs to HONO was proposed.…”
Section: Missing Hono Sourcementioning
confidence: 99%